Investigation of the deformation mechanism of underground excavations in salt and potash mines using in situ deformation measurements - S. Kwon; J. W. Wilson (Canadian Institute of Mining, Metallurgy and Petroleum, 2002)
"In salt and potash mines, the time-dependent deformation mechanism should be clearly understood based on in situ measurements to predict the performance of a mining design. In this study, in situ deformation measurements from the Waste Isolation Pilot Plant (WIPP) and other salt and potash mines were used to determine the transition time from the primary to the secondary creep stage and to investigate the influence of adjacent excavations such as a nearby tunnel excavation, panel excavation and/or pillar extraction on rock deformation. IntroductionThe deformational behaviour of underground excavations in salt and potash mines is complex due to the time-dependency of the rocks. When the material properties are determined from laboratory tests, they should be carefully applied to in situ conditions, because in situ conditions are completely different from laboratory conditions. For instance, in situ deformation measurements show that the deformation rate decreases with time similar to those observed in the laboratory during the early stages. However, the rapid decrease of deformation rate does not come from the microscopic strain hardening effect observed in laboratory tests, but mainly from stress relief around the opening after its excavation (Baar, 1977). It is, therefore, recommended to undertake in situ measurements and use them to understand the deformation mechanism.Even though in situ measurements are widely accepted as important information for understanding the deformation mechanism of salt and potash (Barr, 1971; Kovari and Amstad, 1993), not many publications have focused on the fundamentals of data measurement, the application of the measured data, and the development of data analysis techniques. Recently, several new techniques for better understanding the deformation mechanism of rock salt have been developed that are based on in situ measurements. Kwon and Miller (1995) developed a new technique for describing the actual deformational behaviour of an underground excavation in rock salt. The migration of “zero strain boundary,” which represents a no movement boundary around an underground excavation, could be calculated by the technique developed by Kwon and Miller (1996). Kwon and Wilson (1997, 1998) applied neural network techniques to in situ deformation measurements to predict the deformational behaviour of the underground excavations at the Waste Isolation Pilot Plant (WIPP) located in the United States.In this study, in situ deformation measurementsfrom the WIPP site and other salt and potash mines in the United States were extensively analyzed to understand the deformation mechanism of the underground excavations in the rock mass."